2018
DOI: 10.1108/dta-08-2017-0056
|View full text |Cite
|
Sign up to set email alerts
|

New time-based model to identify the influential users in online social networks

Abstract: Purpose Users are the key players in an online social network (OSN), so the behavior of the OSN is strongly related to their behavior. User weight refers to the influence of the users on the OSN. The purpose of this paper is to propose a method to identify the user weight based on a new metric for defining the time intervals. Design/methodology/approach The behavior of an OSN changes over time, thus the user weight in the OSN is different in each time frame. Therefore, a good metric for estimating the user w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Nodes are the key features in OSN, and the behavior of nodes is strongly related to the behavior of OSN [115]. J. Wu et al [72] proposed a novel framework called Influential Node Identification Link Prediction (INILP) to integrate the identification technique for the famous and influential node.…”
Section: ) Influential Node (In) Methodsmentioning
confidence: 99%
“…Nodes are the key features in OSN, and the behavior of nodes is strongly related to the behavior of OSN [115]. J. Wu et al [72] proposed a novel framework called Influential Node Identification Link Prediction (INILP) to integrate the identification technique for the famous and influential node.…”
Section: ) Influential Node (In) Methodsmentioning
confidence: 99%
“…They defined leadership as the node with the highest degree centrality. However, Mahmoudi, et al, [49] showed that considering the node with the highest degree centrality without considering the weight of each user in each time interval cannot determine who among the nodes (users) is more influential. Nevertheless, the idea presented by Haji Seyed Javadi and colleagues is significant as they proved that the most important users can attract other users.…”
Section: B Dynamic Algorithmsmentioning
confidence: 99%
“…Here, the term user weight refers to the influence of a user in an OSN. In recent years, many researchers have sought to identify the influential users and user weight [49] [76]. This is because "in an OSN, each user has a specific weight, which refers to the influence of the user on the OSN, and the weight of each user is different.…”
Section: Density Of Interactionsmentioning
confidence: 99%
See 2 more Smart Citations